Autoformação como cultivo da vontade: uma perspectiva a partir do homem interior em Agostinho de Hipona - Costa, Daiane Rodrigues (2019)
The study presented here has as its main objective the investigation of human formation in the philosophical works: Literal Commentary to Genesis, the Trinity and the Free Will, by Augustine of Hippo. For this, we approached the notion of anthropology from the mentioned author, his understanding of body and soul (human dimension in the animal man) and lastly, objectified some assumptions of an education of the human being that run through a good will formation. This text is a bibliographic, exploratory and hermeneutic research. Through this, we understood that Augustine conceives the idea of man like a being endowed with body and soul. The soul, when well formed, can lead the individuals to life with wisdom and, therefore, to a beata vita. The will, part of the structure of the human soul for our author, is what move all the other dimensions of the human being and for that it must be well formed. The education of the will, for our thinker, consists in realizing the game of using the objects that serves as the means to something and enjoy or contemplate what is end in itself. With this distinction and cultivation of self, the human will differ from the animal kingdom, which acts by impulse, and guides man well, giving him minimally a detachment relationship with matter. We conclude, therefore, that the Augustinian ethics in the same time that establishes principles for the good acting and achieving a happy life, requires for that a fo rmative process consisting in the education of the will. Once Augustine understands it as free in itself, that is, as selfdetermining, it can turn itself into that which is constant presence, that is, to objects of contemplative forum and to depart, as far as possible, from the dictates of a life submitted to the material world.